Integrative Transcriptomic and Metabolomic Analysis of Muscle and Liver Reveals Key Molecular Pathways Influencing Growth Traits in Zhedong White Geese - Kai Shi; Xiao Zhou; Jiuli Dai; Yuefeng Gao; Linna Gao; Yangyang Shen; Shufang Chen (Animals)
Geese (Anser cygnoides) are popular worldwide with consumers for their unique meat quality, egg production, foie gras, and goose down; however, the key genes that influence geese growth remain elusive. To explore the mechanism of geese growth, a total of 500 Zhedong White geese were raised; four high-weight (HW) and four low-weight (LW) male geese were selected to collect carcass traits and for further transcriptomic and metabolomic analysis. The body weight and average daily gain of HW geese were significantly higher than those of the LW geese (p-value < 0.05), and the yields of the liver, gizzard, glandular stomach, and pancreas showed no significant difference between the HW and the LW group (p-value > 0.05). Compared with the LW geese, 19 differentially expressed genes (DEGs) (i.e., COL11A2, COL22A1, and TF) were detected in the breast muscle from the HW geese, which were involved in the PPAR signaling pathway, adipocytokine signaling pathway, fatty acid biosynthesis, and ferroptosis. A total of 59 differential accumulation metabolites (DAMs), which influence the pathways of glutathione metabolism and vitamin B6 metabolism, were detected in the breast muscle between the HW and LW geese. In the liver, 106 DEGs (i.e., THSD4, CREB3L3, and CNST) and 202 DAMs were found in the livers of the HW and LW groups, respectively. DEGs regulated the pathways of the TGF-beta signaling pathway, pyruvate metabolism, and adipocytokine signaling pathway; DAMs were involved in pyrimidine metabolism, nitrogen metabolism, and phenylalanine metabolism. Correlation analysis between the top DEGs and DAMs revealed that in the breast muscle, the expression levels of COL11A2 and COL22A1 were positively correlated with the content of S-(2-Hydroxy-3-buten-1-yl)glutathione. In the liver, the expression of THSD4 was positively correlated with the content of 2-Hydroxyhexadecanoic acid. In addition, one DEG (LOC106049048) and four DAMs (mogrol, brassidic acid, flabelline, and L-Leucyl-L-alanine) were shared in the breast muscle and liver. These important results contribute to improving the knowledge of goose growth and exploring the effective molecular markers that could be adopted for Zhedong White goose breeding.